2023
DOI: 10.3389/fmicb.2023.1133773
|View full text |Cite
|
Sign up to set email alerts
|

Mitochondrial nanomotion measured by optical microscopy

Abstract: Nanometric scale size oscillations seem to be a fundamental feature of all living organisms on Earth. Their detection usually requires complex and very sensitive devices. However, some recent studies demonstrated that very simple optical microscopes and dedicated image processing software can also fulfill this task. This novel technique, termed as optical nanomotion detection (ONMD), was recently successfully used on yeast cells to conduct rapid antifungal sensitivity tests. In this study, we demonstrate that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 29 publications
0
1
0
Order By: Relevance
“…Cellular nanomotion was highlighted for the first time by attaching living cells to an AFM cantilever and monitoring its oscillations. More recently, our team demonstrated that traditional optical microscopes equipped with a video camera and dedicated software can also detect bacterial [31], fungal [32,33], and mitochondrial [34] nanomotion. This type of nanomotion detection is referred to as optical nanomotion detection (ONMD) [32].…”
Section: Introductionmentioning
confidence: 99%
“…Cellular nanomotion was highlighted for the first time by attaching living cells to an AFM cantilever and monitoring its oscillations. More recently, our team demonstrated that traditional optical microscopes equipped with a video camera and dedicated software can also detect bacterial [31], fungal [32,33], and mitochondrial [34] nanomotion. This type of nanomotion detection is referred to as optical nanomotion detection (ONMD) [32].…”
Section: Introductionmentioning
confidence: 99%